Comparison of lecture and team-based learning in medical ethics education - Ozgonul, Levent (Nursing ethics, 2019)
Background:Medical education literature suggests that ethics education should be learner-centered and problem-based rather than theory-based. Team-based learning is an appropriate method for this suggestion. However, its effectiveness was not investigated enough in medical ethics education.Research question:Is team-based learning effective in medical ethics education in terms of knowledge retention, in-class learner engagement, and learner reactions?Research design:This was a prospective controlled follow-up study. We changed lecture with team-based learning method to teach four topics in a 2-week medical ethics clerkship, while the remaining topics were taught by lectures. For comparison, we formed team-based learning and lecture groups, in which the students and instructor are the same, but the topics and teaching methodologies are different. We determined in-class learner engagement by direct observation and student satisfaction by feedback forms. Student success for team-based learning and lecture topics in the end-of-clerkship exam and two retention tests performed 1 year and 2 years later were compared.Ethical considerations:Ethical approval for the study was granted by Akdeniz University Board of Ethics on Noninvasive Clinical Human Studies Ethics committee.Findings:Short-term knowledge retention did not differ; however, team-based learning was found superior to lecture at long-term retention tests. Student satisfaction was high with team-based learning and in-class engagement was better in team-based learning sessions.Discussion:Our results on learner engagement and satisfaction with team-based learning were similar to those of previous reports. However, knowledge retention results in our study were contrary to literature. The reason might be the fact that students prepared for the end-of-clerkship pass/fail exam (short term) regardless of the teaching method. But, at long-term retention tests, they did not prepare for the exam and answered the questions just using the knowledge retained in their memories.Conclusion:Our findings suggest that team-based learning is a better alternative to lecture to teach ethics in medical education.